Perspectives of gynecologic oncology fellowship training and preparedness for practice - Nancy T. Nguyen; Allyson M. Jang; Tali Pomerantz; Gerald S. Zavorsky; Gary Leiserowitz; Rebecca A. Brooks (Elsevier, 2024)
We aimed to examine the preparedness of recent gynecologic oncology fellowship graduates for independent practice.We conducted a web-based survey study using REDCap targeting Society of Gynecologic Oncology (SGO) members who graduated gynecologic oncology fellowship within the last six years. The survey included 52 items assessing fellowship training experiences, level of comfort in performing core gynecologic oncology surgical procedures and administering cancer-directed therapies. Questions also addressed factors driving participants' selection of fellowship programs, educational experience, research and preparedness for independent practice. A total of 296 participants were invited to complete the survey. Response rate was 42% with n = 124 completed surveys included for analysis. The highest ranked factor for fellowship selection was fit with program 36% (n = 45). Upon completing fellowship, most were uncomfortable performing ureteral conduit formation 84% (n = 103), ureteroneocystostomy 77% (n = 94), exenteration 68% (n = 83), splenectomy 67% (n = 83) and lower anterior resection 41% (n = 51). Most were comfortable managing intraoperative complications 85% (n = 104) and standard cancer staging procedures (range: 61%-99%). Majority were comfortable providing cancer directed therapies with chemotherapy 99% (n = 123), immunotherapy 84% (n = 104), and poly ADP-ribose polymerase (PARP) inhibitors 97% (n = 120). Upon completing fellowship, 77% (n = 95) report having mentorship that met their expectations during fellowship and 94% (n = 116) felt they were ready for independent practice. Majority of fellowship graduates were prepared for independent practice and felt comfortable performing routine surgical procedures and cancer directed treatment. However, most are not comfortable with ultra-radical gynecologic oncology procedures. Maximizing surgical opportunities during fellowship training and acquiring early career mentorship may help.